2015
DOI: 10.4172/2157-7471.1000254
|View full text |Cite
|
Sign up to set email alerts
|

Plants as Antiviral Agents

Abstract: Viruses are microorganisms that infect all kinds of living organisms including plants, and cause remarkable lose in crop production. Although pesticides showed that they can protect plants from pest infections, there are no effective substances that can be used as potent virucides. Therefore, there is a continuous demand to produce chemicals in order to stop and cure viral infections in plants. However, toxicity and carcinogenicity issues were always attributed to chemical pesticides. Screening of natural prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
0
25
0
2
Order By: Relevance
“…Reports of the antiviral activities of plant crude extracts and their constituents against plant viral infection have increased during the last decade [ 32 ]. Many plant extracts of Boerhaavia diffusa , Clerodendrum aculeatum , Mirabilis jalapa , Potentilla arguta , Sambucus racemosa , and Thuja orientalis exhibit inhibitory effects against plant viruses [ 33 , 34 , 35 , 36 , 37 ]. Additionally, several virus-inhibiting compounds, including flavonoids, triterpenoids, alkaloids, and proteins, have been isolated from higher plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of the antiviral activities of plant crude extracts and their constituents against plant viral infection have increased during the last decade [ 32 ]. Many plant extracts of Boerhaavia diffusa , Clerodendrum aculeatum , Mirabilis jalapa , Potentilla arguta , Sambucus racemosa , and Thuja orientalis exhibit inhibitory effects against plant viruses [ 33 , 34 , 35 , 36 , 37 ]. Additionally, several virus-inhibiting compounds, including flavonoids, triterpenoids, alkaloids, and proteins, have been isolated from higher plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rotenone was isolated as the bioactive compound; it is used from early times as pesticides. Plants are large reservoir of secondary metabolites largely untapped or under-tapped for use as pesticide ( Feyisa et al., 2015 ; Waziri, 2015 ). This review portrays and abridges the botanical description, folklore uses and the economic impact of B. verticillata but emphases on its biological activity i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with those of Dunkić et al (2013) as they reported that treating Chenopodium quinoa plants with both Eryngium amethystinum and E. alpinum essential oils prior to inoculation with CMV significantly reduced the number of lesions, with inhibition rates of 80.5 and 77.8%, respectively. The antiviral effect of biocides appears to involve direct inhibition of virus replication, or indirectly through inducing systemic resistance of the host plant against the virus, which may persist for long periods depending on both plant cultivar and the virus strain (Othman and Shoman, 2004;Mahdy et al, 2007;Waziri, 2015). In general, the data presented in Table 3 and 4 indicated that a better inhibitory effect of the investigated biocides was obtained by preinoculation (protective) treatment than the postinoculation (curative) one.…”
Section: Effect Of Biocides On Tnv and CMV Infectivitymentioning
confidence: 99%